The Philosophical Meaning of the Traditional Fire Racing Dance as a Cultural Heritage of Halong Village - Nabila, Syarifah; Subiyakto, Bambang; Mansyur, Mansyur (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to uncover the philosophical meaning and cultural values contained in the Balalap Api Dance, a unique cultural heritage of the Dayak Deah community in Halong Village, Balangan Regency, South Kalimantan. Using a qualitative approach with ethnographic methods, this study combines literature studies, participatory observations, and in-depth interviews with dancers, traditional figures and community members. The result shows that the Balalap Api Dance has a complex philosophical meaning, including the relationship between humans and nature and the spiritual world, the concept of cosmic balance, and the representation of human toughness and resilience. This dance alsp functions as a medium of communication with ancestors and a symbol of the cultural identity of the Dayak Deah. Despite facing the challenges of modernization, the Balalap Api Dance is still preserved as a valuable cultural heritage, reflecting the local wisdom and spirituality of the Dayak Deah community.